2022
DOI: 10.4103/aja2021111
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-specific protein ACTL7A as a biomarker for fertilization outcomes of assisted reproductive technology

Abstract: Obtaining high-quality embryos is one of the key factors to improve the clinical pregnancy rate of assisted reproductive technologies (ART). So far, the clinical evaluation of embryo quality depends on embryo morphology. However, the clinical pregnancy rate is still low. Therefore, new indicators are needed to further improve the evaluation of embryo quality. Several studies have shown that the decrease of sperm-specific protein actin-like 7A (ACTL7A) leaded to low fertilization rate, poor embryo development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…More interestingly, we found that despite mature WT spermatozoa having an acroplaxome, ACTL7A is found almost exclusively on the postacrosomal sheath region of the sperm head in mice ( Fig. 4A ) and was previously reported to also be partially retained in the acroplaxome in humans ( Chen et al , 2021 ; Xin et al , 2022 ). The partial retention of ACTL7A in the human acroplaxome might suggest a divergent function of the protein unique to primates, that the human postacrosomal sheath formation or function is not as reliant in ACTL7A activity, or simply that differences in methodologies and antibodies used may have yielded deviating results.…”
Section: Discussionsupporting
confidence: 65%
“…More interestingly, we found that despite mature WT spermatozoa having an acroplaxome, ACTL7A is found almost exclusively on the postacrosomal sheath region of the sperm head in mice ( Fig. 4A ) and was previously reported to also be partially retained in the acroplaxome in humans ( Chen et al , 2021 ; Xin et al , 2022 ). The partial retention of ACTL7A in the human acroplaxome might suggest a divergent function of the protein unique to primates, that the human postacrosomal sheath formation or function is not as reliant in ACTL7A activity, or simply that differences in methodologies and antibodies used may have yielded deviating results.…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, we found that DEGs (including ACTL7A, ACTRT3, and SPESP1 ) were significantly enriched in cell components, such as the germ cell nucleus and male germ cell nucleus. ACTL7A is essential for early embryonic development, and its reduction could lead to poor embryonic development and even infertility [ 47 , 48 , 49 , 50 ]. The deletion of SPESP1 led to an abnormal distribution of multiple proteins in mouse spermatozoa, reduced the sperm fusion capacity, and reduced the number of pups [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to sperm functional parameters, various markers are being developed and numerous studies are underway to validate their practical use ( Jodar et al, 2017 ; Burl et al, 2018 ; Agarwal et al, 2020 ; Hernandez-Silva et al, 2022 ; Yang et al, 2022 ). Among these, transcriptomic markers are particularly promising due to the well-developed high-throughput techniques used for their analysis and the availability of various on-site validation tools.…”
Section: Introductionmentioning
confidence: 99%